Penilaian Kualitas Layanan Bandara Internasional Ngurah Rai Menggunakan Metode Fuzzy Servqual dan Importance Performance Analysis - Nurfakhrurozi, Rifqi; Andriani, Wahyu; Dewi, Nyoman Indah Kusuma; Saputra, Upayana Wiguna Eka; Adiningrat, Gede Pradiva (Badung Bali: Politeknik Negeri Bali, 2024)
Ngurah Rai International Airport in Bali serves as a critical gateway for tourists, especially in the post-pandemic era. This study evaluates the service quality of the airport using the Fuzzy Servqual and Importance Performance Analysis (IPA) methods. A sample of 100 respondents was analyzed to assess five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that several attributes of the service require improvement, particularly in terms of adequacy of infrastructure, service clarity, and responsiveness to passenger feedback. The IPA analysis identified two attributes as high-priority areas for improvement. Recommendations for enhancing service quality are proposed to better align with passenger expectation and satisfaction.